Development of Field Guide Book Identification of Anuran Species in Lambung Mangkurat KHDTK: The Result of Expert Review - Zainudin Zainudin; Yudi Firmanul Arifin; Atiek Winarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
The forest areas with special-purpose (KHDTK) Lambung Mangkurat University is an important learning resource for many people, especially students. One of the biodiversity in the area that can be utilized is the diversity of Anura. For identified Anuran species, we need the field guide book according to complete with areas character, Anuran list, and supported by the content that is simple and easy to understand. Therefore the field guide book was developed in such a way using the development model by Tessmer. The result of an expert review shows that this field guide book has been very valid (88%) with criteria that can be used without revision. Attractive design, complex content, with simple language make this field guide not only can be used for students but also by the general people.AbstrakKawasan Hutan Dengan Tujuan Khusus (KHDTK) Universitas Lambung Mangkurat merupakan sumber belajar penting bagi banyak pihak, terlebih mahasiswa. Salah satu keanekaragaman hayati di kawasan tersebut yang dapat dimanfaatkan adalah keanekaragaman Anura. Untuk melakukan identifikasi jenis diperlukan buku panduan identifikasi yang sesuai dengan karakter wilayah dan keanekaragaman anura di dalamnya serta ditunjang dengan komponen isi yang sifatnya sederhana dan mudah untuk dimengerti. Oleh karenanya, buku panduan lapangan identifikasi jenis anura ini dikembangkan sedemikian rupa menggunakan model pengembangan oleh Tessmer. Hasil penilaian ahli menunjukkan bahwa buku panduan lapangan ini memiliki kriteria sangat valid (88%) dan dapat digunakan tanpa revisi. Desain menarik, isi yang kompleks, dengan bahasa yang sederhana membuat buku panduan lapangan ini tidak hanya dapat digunakan untuk kalangan pelajar saja namun juga oleh masyarakat umum.